Clinical review and analysis of artery of Percheron infarction - Jing Li; Junling Ge; Shuhui Yang; Guoen Yao (IBRO Neuroscience Reports, 2023)
Artery of Percheron infarction is a rare one of the neurovascular structure variants of acute ischemic stroke characterized by bilateral paramedian thalamic infarcts (BTPI), with or without mesencephalic infarction. Due to the low occurrence rate and various clinical manifestations, the early diagnosis of this disease is often missed. In addition, it is also difficult to diagnose this disease in an early implementation phase because cranial imaging and intracranial vascular imaging may show negative results. So far, its clinical cases have been rarely reported. We systematically reviewed the clinical manifestations, imaging characteristics, anatomical basis, and differentiation diagnosis of the artery of Percheron infarction and reported on three patients and their clinical and radiological medical imaging characteristic findings. We found that most of the infarct lesions in patients with an AOP infraction could not be displayed within a few hours or could not be fully displayed, even the embolism events, most of which showed typical imaging lesions at late review. The decrease of transient consciousness was obvious over the course of the three patients, and the decrease of active communication was also a major feature. Among the three cases, one patient had unilateral upper eyelid ptosis and miosis; the initial symptom of another patient was dizziness; and the other person had decreased computing power after infarction. These clinical symptoms are easily ignored in the diagnosis and treatment of patients with AOP infarction. Therefore, reporting the three clinical cases mentioned above will provide assistance for subsequent research by increasing clinical data.